Zagadnienie długookresowej stabilności finansów publicznych w krajach członkowskich Unii Europejskiej - Baran, Bernadeta (The Long Term Stability Issue of Public Finances in the European Union Countries, 2008)
The aim of this paper was to indicate the place of the long term stability of public finances in EU countries. In the coming decades, ageing populations is projected to have a significant budgetary impact on public finances. It is expected to have a significant impact on growth and lead to pressures to increase public spending. This will make it difficult for member states to maintain sound and sustainable public finances in the long-term. This is of particular importance in Economic and Monetary Union, as high deficits and rising debt in some countries leading to unsustainable public finances might have an adverse impact on macroeconomic conditions for other EMU countries. Therefore, ensuring fiscal sustainability requires time-consistent policies, which involves addressing budgetary imbalances before the budgetary impact of aging sets in. The main problem is that a lot of countries use the positive effects of economic growth and do not cut down the growing expenditures. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 114-124